Factors perceived to influence rural career choice of urban background family physicians: a qualitative analysis - Olga Szafran (Canadian Medical Education Journal, 2019)
Background: Urban background physicians are the main source of physician supply for rural communities across Canada. The purpose of this study was to describe factors that are perceived to influence rural career choice and practice location of urban background family medicine graduates.